МАКТАБГАЧА ТАЪЛИМ МУАССАСАЛАРИ ТАРБИЯЛАНУВЧИЛАРИНИ МИЛЛИЙ ҒОЯ РУҲИДА ТАРБИЯЛАШДА МЕДИАМАХСУЛОТЛАРИ ЎРНИ - Шерманова, Ф. (SCIENCE and SOCIETY, 2020)
The article examines the influence of electronic media on the formation of the outlook of the younger generation. Also the issues of media security were studied.